2020
DOI: 10.18633/biotecnia.v22i2.1245
|View full text |Cite
|
Sign up to set email alerts
|

Inhibición de lipasa pancreática por flavonoides: importancia del doble enlace C2=C3 y la estructura plana del anillo C//Inhibition of pancreatic lipase by flavonoids: relevance of the C2=C3 double bond and C-ring planarity

Abstract: Lipasa pancreática es una enzima clave en el metabolismo de lípidos. Los flavonoides son compuestos bioactivos de gran relevancia debido a sus interacciones con enzimas digestivas. Se evaluó la actividad de lipasa pancreática en presencia de flavonoides. Mediante espectroscopía UVVisible se determinó que el mejor inhibidor fue quercetina, seguido de rutina > luteolina > catequina > hesperetina, con valores de IC50 de 10.30, 13.50, 14.70, 28.50 y 30.50 μM, respectivamente. Todos los flavonoides mostrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Besides the effect of luteolin on insulin secretion via the parasympathetic nervous system that was mentioned previously, , evidence supports the existence of a direct effect of luteolin on pancreatic β cells. ,, An inhibition of luteolin on pancreatic lipase activity (a key enzyme in lipid metabolism) with a low IC 50 value (13.50 μmol/L) has been found via ultraviolet–visible (UV–vis) spectroscopy . In diabetic rats, the pancreatic islet morphology and pancreatic glucose-6-phosphate dehydrogenase (G6PDH) activity can be improved with bioflavonoids, such as luteolin, luteolin 7- O -β-glucoside, and luteolin 7- O -β-glucuronoside .…”
Section: Regulating Role Of Luteolin In Pancreatic Isletsmentioning
confidence: 62%
See 1 more Smart Citation
“…Besides the effect of luteolin on insulin secretion via the parasympathetic nervous system that was mentioned previously, , evidence supports the existence of a direct effect of luteolin on pancreatic β cells. ,, An inhibition of luteolin on pancreatic lipase activity (a key enzyme in lipid metabolism) with a low IC 50 value (13.50 μmol/L) has been found via ultraviolet–visible (UV–vis) spectroscopy . In diabetic rats, the pancreatic islet morphology and pancreatic glucose-6-phosphate dehydrogenase (G6PDH) activity can be improved with bioflavonoids, such as luteolin, luteolin 7- O -β-glucoside, and luteolin 7- O -β-glucuronoside .…”
Section: Regulating Role Of Luteolin In Pancreatic Isletsmentioning
confidence: 62%
“…78,114,115 An inhibition of luteolin on pancreatic lipase activity (a key enzyme in lipid metabolism) with a low IC 50 value (13.50 μmol/L) has been found via ultraviolet−visible (UV−vis) spectroscopy. 116 In diabetic rats, the pancreatic islet morphology and pancreatic glucose-6-phosphate dehydrogenase (G6PDH) activity can be improved with bioflavonoids, such as luteolin, luteolin 7-O-βglucoside, and luteolin 7-O-β-glucuronoside. 117 Moreover, immunohistochemistry staining of the pancreatic tissue for insulin and glucagon revealed that a 16 week treatment with luteolin could reverse HFD-induced pancreatic islet hypertrophy, leading to a decrease in pancreatic insulin and glucagon content, in accordance with the results obtained from plasma insulin and glucagon.…”
Section: ■ Regulating Role Of Luteolin In the Heartmentioning
confidence: 99%
“…Selain itu, beberapa penelitian juga telah melaporkan bahwa senyawa flavonoid memiliki peranan penting dalam menghambat kerja lipase pankreas (Darusman et al, 2001;Zhao et al, 2009). Penelitian pada beberapa jenis senyawa flavonoid menunjukkan bahwa flavonoid dapat menghambat lipase melalui mekanisme penghambatan mixed-type inhibition (Martinez-Gonzaleza et al, 2020).…”
Section: Uji Aktivitas Inhibitor Lipase Pankreasunclassified